Vitamin B12 and Folic Acid Improve Gross Motor and Problem-Solving Skills in Young North Indian Children: A Randomized Placebo-Controlled Trial - Kvestad, Ingrid; Taneja, Sunita; Kumar, Tivendra; Hysing, Mari; Refsum, Helga; Yajnik, Chittaranjan S.; Bhandari, Nita; Strand, Tor A. (PloS one, 2015)
Deficiencies of vitamin B12 and folate are associated with delayed development and neurological manifestations. The objective of this study was to measure the effect of daily supplementation of vitamin B12 and/or folic acid on development in young North Indian children. In a randomized, double blind trial, children aged six to 30 months, received supplement with placebo or vitamin B12 and/or folic acid for six months. Children were allocated in a 1:1:1:1 ratio in a factorial design and in blocks of 16. We measured development in 422 children by the Ages and Stages Questionnaire 3rd ed. at the end of the intervention. Compared to placebo, children who received both vitamin B12 and folic acid had 0.45 (95% CI 0.19, 0.73) and 0.28 (95% CI 0.02, 0.54) higher SD-units in the domains of gross motor and problem solving functioning, respectively. The effect was highest in susceptible subgroups consisting of stunted children, those with high plasma homocysteine (> 10 μmol/L) or in those who were younger than 24 at end study. With the exception of a significant improvement on gross motor scores by vitamin B12 alone, supplementation of either vitamin alone had no effect on any of the outcomes. Our findings suggest that supplementation of vitamin B12 and folic acid benefit development in North Indian Children. ClinicalTrials.gov NCT00717730.